Growth, morphological and physiological responses of alfalfa (Medicago sativa) to phosphorus supply in two alkaline soils - He, Honghua; Peng, Qi; Wang, Xia; Fan, Chenbin; Pang, Jiayin; Lambers, Hans; Zhang, Xingchang (Plant and soil, 2017)
Background and aims Phosphorus (P) deficiency is a major problem for alfalfa (Medicago sativa) productivity on alkaline soils on the Loess Plateau, China. Our aim was to investigate growth, morphological and physiological responses of alfalfa to P supply in two alkaline soils when water supply is limited. Methods A pot experiment was carried out to grow alfalfa in two alkaline soils supplied with different rates of P. Parameters of plant growth and root morphology, rhizosphere pH and carboxylates, and plant concentrations of mineral nutrients were measured. Results Plant growth and nutrient uptake were enhanced by supplying P, but shoot growth was not further increased when P supply was >20 μg P g−1 soil. Specific root length was only responsive to changes in soil P when P supply was low in the loessial soil. The rhizosphere carboxylate amount was significantly greater when no P was supplied than when P was supplied to the loessial soil. The rhizosphere pH was lower than the bulk soil pH, but did not vary with soil P. Conclusions A P supply of 20 μg P g−1 soil was optimal for alfalfa growth. The responses of specific root length and rhizosphere carboxylates depended on soil type.